HPV detection in floor of mouth squamous cell carcinoma by PCR amplification - Simonato, Luciana E.; Tomo, Saygo; Garcia, José Fernando [UNESP]; Veronese, Luiz Alberto [UNESP]; Miyahara, Glauco I. (GN1 Sistemas e Publicacoes, 2016)
Introduction: Studies conducted during the last years, using new technologies for viral detection, permit to consider human papillomavirus (HPV) an etiologic factor for cervical cancer. Besides the relation to genital regions, other anatomic sites have been associated with HPV, including head and neck regions. Objectives: To investigate the prevalence of HPV infection in 35 samples from paraffin-embedded tissues using polymerase chain reaction (PCR)-deoxyribonucleic acid (DNA) amplification, and correlate it with demographic, clinical, and morphological factors and prognosis. Materials and methods: All samples were first amplified with human β-globin gene primers. Samples with positive amplification were subjected to HPV-DNA detection with general GP5 and GP6 primers. Results: Only 30 samples were amplified for the β-globin gene. No floor of mouth squamous cell carcinoma cases showed amplification of HPV DNA. Discussion: The absence of HPV-DNA amplification does not suggest that this virus is absent from the process of oral carcinogenesis, since the selected sample is not in the risk group for the development of oral cancer associated with HPV infection. Conclusions: No correlation was found between HPV infection and floor of mouth carcinogenesis, however further studies are necessary.
Keywords: Hpv-DNA tests; Mouth neoplasms; Polymerase chain reaction; Squamous cell carcinoma